1980
DOI: 10.1177/00220345800590090401
|View full text |Cite
|
Sign up to set email alerts
|

Setting and Thermal Reactions of Phosphate Investments

Abstract: The setting reactions and thermal degradation of the phosphate binders are interpreted from the DTA and X-ray diffraction data. Setting takes place through complex formation of (NH4Mg PO4.6H2O)n, excess reactants, and water. Dehydration and thermal reactions lead to a sequence of reactions forming (NH4MgPO4.H2O)n, (Mg2P2O7)n, Mg2P2O7, and Mg3(PO4)2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…4); again, no crystalline reflections were identified that could be associated with a dehydrated KMgPO 4 phase. As discussed above, it is postulated that KMgPO 4 is non-crystalline between 200 °C -700 °C [25][26][27] , as a result of dehydration of struvite-K. Diffuse scattering associated with the glassy slag fraction is reported between 24 , however the diffuse scattering in the 200 °C diffraction pattern was evident over a wider range (between ), suggesting that more than one amorphous phase could be present. The quartz identified at 200 °C is believed to be contamination from the cleaning media (sand) used during grinding.…”
Section: Omentioning
confidence: 98%
“…4); again, no crystalline reflections were identified that could be associated with a dehydrated KMgPO 4 phase. As discussed above, it is postulated that KMgPO 4 is non-crystalline between 200 °C -700 °C [25][26][27] , as a result of dehydration of struvite-K. Diffuse scattering associated with the glassy slag fraction is reported between 24 , however the diffuse scattering in the 200 °C diffraction pattern was evident over a wider range (between ), suggesting that more than one amorphous phase could be present. The quartz identified at 200 °C is believed to be contamination from the cleaning media (sand) used during grinding.…”
Section: Omentioning
confidence: 98%
“…The inclusion of FA in MKPC enhances the workability of the binder via the "ball-bearing effect" of the spherical particles [6,[9][10][11]. Several studies [6,12,13] based on FA/MKPC blended binders have suggested that FA simply acts as a diluent or inert filler, that modifies the aesthetics of MKPC to be compatible to traditional Portland cement, which has been deemed important for rapid-repair applications [9]. Conversely, others hypothesise that FA replacement promotes high mechanical strength in FA/MKPC binders, as a consequence of the formation of a secondary amorphous phase containing silicon-phosphate bonds [12,14].…”
Section: Introductionmentioning
confidence: 99%
“…To date, research and development is still ongoing for new investment materials which would bring casting quality and accuracy to new heights. For phosphate-bonded investments, numerous investigations have been carried out to examine the following in an unrelenting search for improvements and betterments: effects of mixing methods and mixing conditions on the setting expansion and compressive strength of casting investments 11,12) , effects of the properties/characteristics of casting investments on cast smoothness and dimensional accuracy 11) , reaction of investment with cobalt-chromium alloys at high casting temperatures 13) , factors which affect the setting and thermal expansions of casting investments 14,15) , effects of investment's potential expansion, hot strength, and deformation at elevated temperatures on casting accuracy 16,17) , and factors which influence the gas permeability and castability of casting investments 18,19) . One of the recent innovations in investment casting was the rapid-heating phosphate-bonded investment 20) .…”
Section: Introductionmentioning
confidence: 99%